A Lucas todo le sale mal - Puga, Maria Luisa, 1944-2004.; Schikora, Stefanie (Mexico, D.F. : Fondo de Cultura Economica, 2005)
Lucas has very bad luck until one day when he finds a special amulet that could change his fortune.
Keywords: Fortune -- Spanish language -- Juvenile fiction; Amulets -- Spanish language -- Juvenile fiction; Fiction. -- Amulets; Fiction. -- Luck